A Mucosal Adenovirus Prime/Systemic Envelope Boost Vaccine Regimen Elicits Responses in Cervicovaginal and Alveolar Macrophages of Rhesus Macaques Associated With Delayed SIV Acquisition and B Cell Help - Hunegnaw, Ruth; Helmold Hait, Sabrina; Enyindah-Asonye, Gospel; Rahman, Mohammad Arif; Ko, Eun-Ju; Hogge, Christopher J.; Hoang, Tanya; Robert-Guroff, Marjorie (Frontiers in Immunology, 2020)
Vaccine strategies targeting the mucosal portal of entry may prevent HIV acquisition and systemic infection. Macrophages in cervicovaginal compartments are one of the first cell types to encounter virus upon vaginal exposure. Their activation can lead to recruitment of additional macrophages and CD4+ T-cells susceptible to viral infection. However, they are also critical in providing early protection against invading pathogens. Therefore, understanding their response to immunization is important for vaccine design. We immunized rhesus macaques twice mucosally with replicating adenovirus (Ad) SIV recombinants, followed by two intramuscular boosts with SIV gp120 protein. Macaques were subsequently challenged intravaginally with repeated low doses of SIVmac251. Using flow cytometry, we evaluated responses of cervicovaginal macrophages (CVM) and alveolar macrophages (AM) in bronchoalveolar lavage as initial immunization was to the upper respiratory tract. The frequency of CVM increased over the course of immunization; however, CCR5 expression significantly decreased. Significantly increased expression of the chemokines CCL3 (p<0.01), CCL4, CCL5 and CXCL8 (p<0.0001 for all) on CVM was seen post-1st Ad but their expression significantly decreased post-2nd boost. CD4+ T-cell frequency in the cervical mucosa remained unchanged. CVM FcγRIII expression was significantly increased at all time points post-immunization compared to naïve animals. FcγRIII expression post-2nd Ad positively correlated with the number of challenges needed for infection (r =0.68; p=0.0051). Vaccination increased AM FcγRIII expression which post-2nd boost correlated with antibody-dependent phagocytosis. Activation of AMs was evident by increased expression of CD40 and CD80 post-2nd Ad compared to naïve macaques. APRIL expression also significantly increased post-2nd Ad and correlated with B cell frequency in BAL (r=0.73; p=0.0019) and total IgG in BAL-fluid (r=0.53; p=0.047). B cells cultured with SIV gp120-stimulated AM supernatant from vaccinated macaques exhibited significant increases in B cell activation markers CD38 and CD69 compared to B cells cultured alone or with AM supernatant from unvaccinated macaques. Overall, the vaccine regimen did not induce recruitment of susceptible cells to the vaginal mucosa but increased CVM FcγRIII expression which correlated with delayed SIV acquisition. Further, immunization induced expression of AM cytokines, including those associated with providing B cell help.